2020
DOI: 10.3390/educsci10040090
|View full text |Cite
|
Sign up to set email alerts
|

Testing the KAPS Model of Reading Comprehension in a Turkish Elementary School Context from Low Socioeconomic Background

Abstract: This correlational study aimed to explore the relations of background knowledge, automaticity (rate), prosody, and strategy use with reading comprehension (KAPS model of reading comprehension) in the written Turkish language context with 207 fourth grade students. Successful comprehension requires readers to make meaning out of what they read. Our KAPS model of reading comprehension hypothesizes relations of background knowledge, fluency components (rate and prosody), and strategy use with reading comprehensio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 33 publications
(41 reference statements)
1
4
0
Order By: Relevance
“…Successful comprehension requires readers to make meaning out of what they read. The study affirms the importance of automaticity in word recognition and comprehension strategies in contributing to reading comprehension (Yildirim et al, 2020).…”
Section: The Exploration Stagesupporting
confidence: 76%
“…Successful comprehension requires readers to make meaning out of what they read. The study affirms the importance of automaticity in word recognition and comprehension strategies in contributing to reading comprehension (Yildirim et al, 2020).…”
Section: The Exploration Stagesupporting
confidence: 76%
“…They have shown that it is not enough to just read the text mechanically, but it is also necessary to think about the communicated information concerning known and unknown words, contexts, and meaning. Yildirim, Cetinkaya, et al (2020) identified the KAPS model and developed factors contributing to reading comprehension, such as the use of deep reading.…”
Section: Discussionmentioning
confidence: 99%
“…These roles are believed to be effective in promoting children's reading development from the aspect of fluency (National Reading Panel, 2000;Henry, 2008;Pagan & Sénéchal, 2014;Sawyer et al, 2018;Brown et al, 2019;Zambrana et al, 2019;Yildirim et al, 2020), comprehension (National Reading Panel, 2000Gabl et al, 2007;Henry, 2008;Shany & Biemiller, 2009;Blanch et al, 2013;Pagan & Sénéchal, 2014;Brown et al, 2019;Yildirim et al, 2020) and interest (Cotter, 2012;Yeo, Ong & Ng, 2014;Levy, Hall & Preece, 2018;Choi, Kang & Sheo, 2020;Dobbs-Oates, Pentimonti, Justice and Kaderavek, 2015;Kathy, 2016). Traditionally, the roles as a motivator, tutor and facilitator in young learner's reading were given larger emphasis on the teachers in the classroom.…”
Section: Discussionmentioning
confidence: 99%
“…Parents who function as a continuous motivator and consistent reading tutor increases children's interest to induce questions during reading (Cotter, 2012), thus able to read with automaticity and prosody (Brown et al, 2019;Yildirim et al, 2020) that leads to a better comprehension skill. Additionally, parents' role is also impactful in building the interest of reading among the children.…”
Section: Reading Problems Aided By Parents In Young Children's Readin...mentioning
confidence: 99%